THE ROLE OF PARENTS IN NURTURING STUDENTS’ SOCIAL QUOTIENT: CARING - Heri Miarto (Journal of English Language Teaching and Islamic Integration, 2025)
This article aims to examine the role of parents in fostering  social  concern  among  elementary  school  children based  on  literature  review  from various  relevant  journals. Social care is a vital character value that should be instilled from an early age, and the family as the first environment plays a key role in shaping children's character. The research method used  is  a literature  review  with  a  descriptive  qualitative approach. The findings show that parents play a strategic role in  fostering  children's  caring  attitudes through  exemplary behavior,  communication,  habituation  of  social  values,  and active involvement in children's social activities. This article also  includes  a  reflection  instrument  for  parents  to  support implementation at home.